Diversity of Segetal Flora in Salix viminalis L. Crops Established on Former Arable and Fallow Lands in Central Poland - Maria Janicka; Aneta Kutkowska; Jakub Paderewski (Agriculture, 2021)
The flora of willow (Salix viminalis L.) plantations consists of various plant groups, including plants related to arable land, called segetal plants. Knowledge of this flora is important for maintaining biodiversity in agroecosystems. The aim of the study was to assess the segetal flora of the willow plantations in central Poland, depending on the land use before the establishment of the plantations (arable land or fallow) and the age of the plantations. Moreover, the aim was also to check for the presence of invasive, medicinal, poisonous and melliferous species. The vegetation accompanying willow was identified based on an analysis of 60 phytosociological relevés performed using the Braun-Blanquet method. For each species, the following parameters were determined: the phytosociological class; family; geographical and historical group; apophyte origin; biological stability; life-form; and status as an invasive, medicinal (herbs), poisonous or melliferous species. The results were statistically processed. Segetal species accounted for 38% of the flora accompanying willow. The plantations on former arable land were richer in segetal species than those on fallow. Mostly, short-lived and native species dominated. In line with the age of the plantations, the number of segetal species decreased. The share of apophytes increased, and anthropophytes decreased. Furthermore, many valuable plants were found among the flora accompanying willow.